GENRE-BOUND STYLE SHIFTS: COMPARATIVE COSTUME ANALYSIS IN HISTORICAL AND CONTEMPORARY BOLLYWOOD FILMS - Burad, Ranu; Saxena, Aastha; Pareek, Aditi; Choudhary, Rama; Sharma, Babita (ShodhKosh: Journal of Visual and Performing Arts, 2026)
Costume design is an essential visual narrative element in the film, which aids in the character building, cultural representation, and theme expression. This paper analyzes the history of the costume aesthetics in the Bollywood films of the same genre over the time featuring an emphasis on the determination of the shifts in the style depending on the genre. The qualitative research method is applied, and the chosen films are analyzed comparatively in visual and textual forms. The research compares the films Mughal-e-Azam (1960) and Jodha Akbar (2008) as the works of historical genre, and Umrao Jaan (1981/2006) and Gangubai Kathiawadi (2022) as the films of contemporary cultural narratives. The results demonstrate that there is a major shift in the mode of costuming, where the designs are stylized, spectacle oriented, to being research based and authentic as well as character-centred. The costume design in historical films has developed not only theatrical spectacles to the depiction of the actual historical events based on the research and the use of modern technologies in the movie industry. The same can be applied to the modern narratives, where imagining femininity becomes less decorated and ideal, and more symbolic, minimalistic, and psychologically based. Modern Bollywood cinema costume design is becoming an important narrative element, which displays the characterization of change, socio-cultural processes, and gender identity. The paper notes the increased significance of authenticity, symbolism and narrative integration in costume design due to technological developments, professional experience and shifting audience demands. The notion of the genre-bound style shift highlights the way the aesthetics of costumes would be changed as a part of the genre structure when accommodating a larger cultural and cinematic shifts. On the whole, the work underlines the idea that the costume design ceased to be only ornamental but a focus of the development of the history of visual language and narration of modern Bollywood movies.